For the importance of fishing related to disasters: collapse of the dam of Fundão Mariana-MG (Research, Society and Development, 2023)
The main source of environmental pollution is human activities that affect the environment, these pollutants accumulate, changing not only the characteristics of air, water and soil, but also causing damage to human health and causing toxicity to aquatic organisms. Among the activities that cause environmental pollution, mining stands out, which alters the quality of the ecosystem and produces an abundant amount of waste that usually remains in the dam. When these dams break, they create big problems. On November 5, 2015, in the region of Mariana, in Minas Gerais, the Brazilian mining company suffered its worst accident. The Samarco Mineradora dam broke and leaked about 43 million cubic meters of mining waste (clay and sand) rich in iron, aluminum, manganese and other metals. The destruction of the Fundão Dam caused an immeasurable social, environmental, cultural and economic disaster in Mariana, in the district of Bento Rodrigues and in 41 other municipalities, leaving a trail of destruction along the Rio Doce until it reached the ocean. Several people find themselves homeless, not counting those who lost their lives in the tragedy, 19 people. The ecosystemic impacts caused are invaluable and inconvertible. In view of the questions of the affected population, the objective of this research is to extract the lessons of the disaster to show the continued importance of academic studies for the contribution and improvement of the society affected by the disaster. This research deals with a bibliography review. The systematic bibliographic review is a scientific method to search for the analysis of articles in a certain area of science.